THE USE OF INSTAGRAM FOR ASYNCHRONOUS MEETINGS TO ENGAGE STUDENTS IN DISCUSSION & STRENGTHEN STUDENTS' SPEAKING SKILL - Riyani; Sri Handayani (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
The objective of this research is to know whether the use of Instagram can strengthen thestudents' speaking skills when it is implemented as asynchronous meeting in teaching learningprocess. This research used a Classroom Action Research which was implemented in twocycles. The subject of the research was class 01 Semester II, English Education Program,Teacher Training and Education Faculty, UNISRI, Surakarta in 2020/2021 Academic Year. Thisstudy was conducted in two cycles. The first cycle consists of four meetings, and the secondcycle consists of three meetings. The procedure of the action research consists of planning,acting, observing and reflecting. The data were collected through questionnaire, interview, fieldnotes, and tests. To analyze the quantitative data, the researcher used descriptive statistics. Itwas used to compare the scores and means of pre-test and post-test.The result of the research showed that the use of Instagram has helped students to strengthentheir speaking skills. Some of the advantages of using Instagram are as follows: (1) Students'pronunciation in English has been significantly improved. Some vocabularies in English thatwere previously always mispronounced, after posttest II, it almost didn't happen anymore, (2)Students who were previously unfamiliar with discussion are now more accustomed toexpressing their ideas or opinions in front of others, (3 ) Students also look more confident whenthey have to speak English because they can use correct pronunciation, (4) the use ofInstagram also improves students' listening skills, because they often listen to videos, students'listening skills also get better. It can be said that the use of this Podcast media is quitesuccessful.Keywords : Instagram, Speaking Skill, Action Researc